Studies on Certain Aspects of Nutritive Value of Indian Halibut, Psettodes erumei with Special Reference to its Body Asymmetry - M., Das; B., Mishra (Fishery Technology, 2025)
Psettodes erumei contains 18.79 % of protein. Its fat content is only 0.55% The mineral content is quite comparable to other marine fishes with the exception of low calcium content. Outstanding among all the modifications is the asymmetrical distribulion of fat. Fat content on the blind side is about 70% higher than that of ocular side. Fat, phosphorus and potassium exhibit regional variations in their distribution. The fish has 56.24%, edible portion and that of ocular sideis about 23% higher than that of blind side.